A poetry of remembrance : a study of Tatamkhulu Afrika's Nine Lives, Dark Rider and Maqabane - Radloff, Adeline (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2002.